Fostering academic success through Service Learning activities - Emanuela M. Torre; Paola Ricchiardi (Firenze University Press, 2023)
This article illustrates the Service Learning model developed by a research group of the Department of Philosophy and Educational Sciences of the University of Turin for the implementation of projects (Fenix, Nobody Stays Behind, Un Assist towards success, Peer Will, A playful course to introduce Italian Language), which actively involved numerous university students, to meet the learning needs of disadvantaged children and young people in their community (n=2.673). It is an original model, which integrates the quality elements of Service Learning identified by international studies, with peculiar characteristics, such as the need to balance the educational nature of the experience for university students with the quality of the intervention carried out and the systematic nature of the research monitoring. In this contribution, the impacts both on the direct beneficiaries and on the university students involved will be presented.   Promuovere il successo scolastico attraverso programmi di Service Learning. Il presente articolo illustra il modello di Service Learning elaborato da un gruppo di ricerca del Dipartimento di Filosofia e Scienze dell'educazione dell'Università di Torino per la realizzazione di progetti (Fenix, Nessuno Resta Indietro, Un Assist verso il successo, Peer Will, Programma ludico per l'arricchimento linguistico), che hanno coinvolto attivamente numerosi studenti universitari, per far fronte ai bisogni di apprendimento di bambini e ragazzi svantaggiati della loro comunità di appartenenza (n=2.673). Si tratta di un modello originale, che integra gli elementi di qualità del Service Learning individuati da studi internazionali, con caratteristiche peculiari, quali l'istanza di bilanciamento del carattere formativo dell'esperienza per gli studenti universitari con la qualità dell'intervento condotto e la sistematicità del monitoraggio di ricerca. Verranno presentati in questo contributo gli impatti sia sui beneficiari diretti che sugli studenti universitari coinvolti.